POTENSI TINTA GURITA (OCTOPUS SP.) SEBAGAI IMUNOSTIMULAN PADA UDANG VANAME (LITOPENAEUS VANNAMEI) - RANGGA IDRIS AFFANDI; MOHAMAD FADJAR; NURI MUAHIDDAH; BAGUS DWI HARI SETYONO (GANEC SWARA, 2023)
Vaname shrimp (Litopenaeus vannamei) is an export commodity from the fisheries sub-sector which has high economic value. The development of aquaculture systems from traditional to intensive has the potential for disease attacks. Control of the spread of the disease must be done as early as possible, one method of prevention is using immunostimulants. An alternative source of immunostimulants that can be used to increase the immune system of shrimp is octopus (Octopus sp.) ink. Octopus ink is generally not used or thrown away when the octopus meat is processed. Research on octopus ink is also minimal compared to squid ink and cuttlefish ink. The purpose of this review is to provide an overview of the potential of octopus ink as an immunostimulant for vaname shrimp. It is known that the content of octopus ink consists mostly of alkaloids, melanin, amino acids, and carboxylic acids. Octopus ink has various roles based on its compound content such as antimicrobial, antioxidant, antibacterial, antiretroviral, anticancer, anti-ulcerogenic, anti-inflammatory, antivirus, antifungal, antiviral, and anti-proliferative. From the results of the literature study, it is explicitly necessary to carry out further research to find out more complete compounds content in octopus ink so that its potential as an immunostimulant in vaname shrimp cultivation can be identified more clearly.